(untitled) (Cardiovascular Journal, 2021)
Background: Vitamin D are needed for normal functioning of cardiovascular system, and its deficiency has been linked to different cardiovascular disorders, including hypertension. However, the relationship between vitamin D deficiency and ischaemic heart disease is not yet clear. The present study was intended to find out the association between serum vitamin D level and acute coronary syndrome (ACS). Methods: The cross-sectional analytical study was carried out in a tertiary care hospital of Dhaka, Bangladesh. Fifty-one consecutive ACS patients admitted into the Department of Cardiology of the hospital were considered as the cases and 51 apparently healthy subjects were considered as the controls. The exposure and outcome variables were serum vitamin D and ACS respectively. Vitamin D insufficiency and deficiency were defined as serum 25(OH) D <30-20 ng/ml and <20 ng/ml, respectively. Severe vitamin D deficiency was defined as serum 25(OH) D <10 ng/ml. Results: Hypovitaminosis D was prevalent in both cases and controls; however, the mean serum 25(OH) D was significantly lower in the former than the latter (14.2 ± 5.9 ng/ml vs. 18.2 ± 6.3 ng/ ml, respectively; p <0.001). Vitamin D insufficiency and moderate deficiency (serum 25(OH) D <20- 10 ng/ml) did not differ significantly between the groups, but severe deficiency (<10 ng/ml) was significantly more common in patients with ACS compared to the healthy controls. The risk of having moderate and severe vitamin D deficiency was 1.9-fold (95% CI = 0.8 – 4.7) and 22.8-fold (2.9 – 180.4) higher for ACS patients than for healthy subjects (p = 0.173 and p <0.001, respectively). Conclusion: Vitamin D deficiency is more common in patients with ACS compared to those without ACS. However, the independent association between vitamin D deficiency and ACS needs further evaluation. Cardiovasc. j. 2021; 13(2): 183-188